Urdu ka guldasta - Motia : for class 1 . - Fozia Ahsaan Farooqi (Karachi ; Oxford university press, 2021)
Urdu Ka Guldasta Motia is a celebrated book that highlights the beauty and diversity of Urdu literature. It features selected works from various poets and writers, showcasing the elegance and depth of the Urdu language. The author compiles different aspects of Urdu literature, including ghazals, poems, and prose, creating a delightful bouquet that serves as a valuable resource for literature enthusiasts while also guiding new readers. The book emphasizes the historical and cultural significance of Urdu, reflecting human emotions and experiences through the lens of literature.
Keywords: Urdu - text book; Urdu - grammar; Urdu - literature